Gwen Verdon a life on stage and screen - Shelley, Peter (McFarland & Company, 2015)
"Stricken with rickets as a child, Verdon overcame severe leg deformity through ballet training, making her film debut at 11 as a solo ballerina in the musical The King Steps Out (1936). This full-length biography of Verdon covers her life and career, her individual performances and her collaborations with choreographers Jack Cole and Bob Fosse, her husband"...